3-Glucosylated 5-amino-1,2,4-oxadiazoles: synthesis and evaluation as glycogen phosphorylase inhibitors - Donnier-Maréchal, Marion; Goyard, David; Folliard, Vincent; Docsa, Tibor; Gergely, Pal; Praly, Jean-Pierre; Vidal, Sébastien (Beilstein Journal of Organic Chemistry, 2015)
Glycogen phosporylase (GP) is a promising target for the control of glycaemia. The design of inhibitors binding at the catalytic site has been accomplished through various families of glucose-based derivatives such as oxadiazoles. Further elaboration of the oxadiazole aromatic aglycon moiety is now reported with 3-glucosyl-5-amino-1,2,4-oxadiazoles synthesized by condensation of a C-glucosyl amidoxime with N,N’-dialkylcarbodiimides or Vilsmeier salts. The 5-amino group introduced on the oxadiazole scaffold was expected to provide better inhibition of GP through potential additional interactions with the enzyme’s catalytic site; however, no inhibition was observed at 625 µM.
Keywords: amidoxime; carbodiimide; glycogen phosphorylase; oxadiazole; Vilsmeier salt